Application of STEM-PjBL Based Chemistry Module to Improve Science Literacy and Student Learning Motivation - Ratu Evina Dibyantini; Susilawati Amdayani; Muhammad Isa Siregar; Dewi Syafriani (Postgraduate, University of Mataram, 2023)
The purpose of this study is to determine the application of the use of STEM-PjBl-based chemistry modules in improving science literacy and student learning motivation. The subjects of this study were 2nd semester students in the 2022/2023 academic year who attended general chemistry lectures on the topic of organic compounds. There are 92 students divided into 3 classes. The research method uses a quantitative approach with a quasi-experimental design in the form of a one group pretest and posttest design. The instruments used in the study were science literacy test and learning motivation questionnaire. The research data were analyzed statistically and descriptive statistics including the calculation of N-Gain and percentage. Based on the results of data analysis, the increase in student science literacy was 0.46 with moderate criteria. Science literacy skills that increased significantly were in the aspect of explaining scientific phenomena by 81%. The application of STEM-PjBL-based chemistry modules also increases student learning motivation with an average of 76% before learning to 87% after learning. It can be concluded that using STEM-PjBl-based chemistry modules can help students improve science literacy and learning motivation in organic compound materials.